2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24071
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Problem Framing on Solution Shifts: A Case Study

Abstract: Samuelina Wright is a senior in Mechanical Engineering at the University of Michigan. She has worked in design and ideation research for over a year. Her focus has been on quantifying the diversity of solution sets, studying design problem framing, and exploring paradigm relatedness. She is interested in engineering education, which is where her passion for teaching and her technical background in engineering overlap. As an engineering designer herself, she is interested in understanding individuals' ideation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Altering perspectives about a problem description to reveal patterns of reasoning and problem solving that are associated with a particular way of "seeing" the problem, and leading to a possibility to "act" within the situation 11,14,[30][31][32][33] Problem defining…”
Section: Problem Findingmentioning
confidence: 99%
“…Altering perspectives about a problem description to reveal patterns of reasoning and problem solving that are associated with a particular way of "seeing" the problem, and leading to a possibility to "act" within the situation 11,14,[30][31][32][33] Problem defining…”
Section: Problem Findingmentioning
confidence: 99%
“…The DPF is grounded in research on cognitive styles and problem framing, and it was originally used to understand how the framing of a design challenge affects ideation and solution generation 67,68 . The DPF breaks design challenges into three components: (1) context, (2) need, and (3) goal.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Context refers to who needs a solution and what purpose the solution serves, need refers to functional requirements and constraints of the design challenge, and goal refers to the instructions used to generate ideas and the metrics used to evaluate those ideas. In an experiment studying the effect of DPF on ideation metrics such as paradigm relatedness, researchers demonstrated that the DPF can successfully shift students' ideas based on the framework provided 68 . Because our work is exploring prototyping methods, we adapted the DPF into three separate frames, one for each of our three lenses (i.e., desirability, feasibility, and viability); the problem frames used in this study are shown in Appendix A.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In our prior work, we utilized individual's reflections on their ideation process to qualitatively characterize their approach and how that approach changed from on situation to the next. 7 We build on that work by focusing this study on developing a quantitative measure for assessing a shift strictly in terms of the design outcomes that the individual exhibits-the ideas that they produce in different design situations. To measure an ideation shift, one first needs to understand what is someone's baseline/default outcomes in some neutral situation.…”
Section: Introductionmentioning
confidence: 99%